Combine like terms
2x^2 + -7x^2 = -5x^2
-9x + 4x = -5x
3 + -2 = 1
put back together
-5x^2 - 5x +1
Answer:
(4,-7)
Step-by-step explanation:
-w=(5,-3)
-z=(-1,-4)
so -w-z=(5-1,-3-4)
Your answer would be either A...or D.
The equivalent expression of (8x)^-2/3 * (27x)^-1/3 is 1/12x
<h3>How to evaluate the expression?</h3>
The expression is given as:
(8x)^-2/3 * (27x)^-1/3
Evaluate the exponent 8^-2/3
(8x)^-2/3 * (27x)^-1/3 = 1/4(x)^-2/3 * (27x)^-1/3
Evaluate the exponent (27x)^-1/3
(8x)^-2/3 * (27x)^-1/3 = 1/4(x)^-2/3 * 1/3(x)^-1/3
Multiply 1/4 and 1/3
(8x)^-2/3 * (27x)^-1/3 = 1/12(x)^-2/3 * (x)^-1/3
Evaluate the exponent
(8x)^-2/3 * (27x)^-1/3 = 1/12(x)^(-2/3 -1/3)
This gives
(8x)^-2/3 * (27x)^-1/3 = 1/12(x)^(-1)
So, we have
(8x)^-2/3 * (27x)^-1/3 = 1/12x
Hence, the equivalent expression of (8x)^-2/3 * (27x)^-1/3 is 1/12x
Read more about equivalent expression at
brainly.com/question/2972832
#SPJ1
Answer:
23
Step-by-step explanation: